Polymastiidae and Suberitidae (Porifera: Demospongiae: Hadromerida) of thedeep Weddell Sea, Antarctic - Plotkin, Alexander S.; Janussen, Dorte (Zootaxa, 2008)
The Antarctic deep-water fauna of Polymastiidae and Suberitidae is revised using recently collected material from the Weddell Sea. The former family appeared to be more abundant and diverse than the latter family in the studied area. Seven species within five polymastiid genera and three species within three suberitid genera are described. Relatively high sponge abundance at two stations deeper than 4700 m was mainly constituted by a polymastiid species Radiella Antarctica sp. nov. Previously, representatives of Radiella have never been found in the Antarctic. An eurybathic species, Polymastia invaginata, well known from the Antarctic and subantarctic, appeared to be especially abundant at less than 1000 m depth. Another eurybathic polymastiid species, Tentorium cf. semisuberites, known for its bipolar distribution, was the third abundant species at the depths between 1000–2600 m, with the highest density found at the deeper stations. Tentorium papillatum, endemic of the Southern Hemisphere, was registered only at a depth of about 1000 m. Other species studied were less abundant. Astrotylus astrotylus, the representative of the endemic Antarctic genus, was found exclusively deeper than 4500 m, often together with R. antarctica. Acanthopolymastia acanthoxa, the endemic deepwater Antarctic species, was registered at 3000 m. The discovery of suberitid Aaptos robustus sp. nov. at about 2300 m is the first signalization of Aaptos in the Antarctic and at such a considerable depth. The finding of Suberites topsenti deeper than 4700 m is also remarkable. In general the results achieved confirm the high degree of geographical endemism of the Antarctic deep-water sponge fauna and the eurybathic distribution of many Antarctic sponge species.